THALASSEMIA MINOR SCREENING APPLICATION USING THE C4.5 METHOD BASED ON LARAVEL - Sohputro, Nicolas; Wijayanto, Bangun; Kurniawan, Yogiek Indra (Jurnal Teknik Informatika (Jutif), 2024)
Thalassemia is an inherited blood disorder that causes anaemia and weak red blood cells. Thalassemia minor is a type of thalassemia where the patient is a carrier of thalassemia and only experiences mild anaemia. To prevent an increase in the number of thalassemia cases, a screening process is held for an individual to confirm whether there is a thalassemia carrier in the body. In providing screening in Banyumas Regency, the Unsoed Medical Faculty Thalassemia Research Team encountered several problems, namely that the screening results could only show whether an individual was a carrier of thalassemia minor or not. This causes a problem because a good screening result is a probability. The second problem is the absence of an integrated information system for thalassemia control in Banyumas Regency. The solution to these two problems is to build a thalassemia minor screening application. The application uses the C4.5 data mining method to calculate the likelihood of thalassemia minor in individuals. The application is made website-based using Laravel to speed up website development. The system also uses a web service to be able to access the created C4.5 algorithm.